Pemberdayaan Ekonomi Rumah Tangga Melalui Pengolahan Sampah Anorganik Menjadi Kerajinan Bernilai - Racmi, Seci Lia; Hijeria, Putri; Alamsyah , Alif Novliyan; Maulana, Sidik; Lestari, Dwi Puji; Wagini, Wagini; Soleh, Ahmad; Suwarni, Suwarni (Jurnal Kewirausahaan & Inovasi, 2025)
This community service program was implemented in RT 24 RW 4, Pematang Gubernur Subdistrict, Bengkulu City, with the aim of empowering household economies through the creative recycling of inorganic waste into valuable crafts. The activity focused on plastic bottle caps, a commonly found waste material in households, which were transformed into tote bags. The program applied a participatory approach, where residents especially housewives were actively involved in collecting materials, attending training sessions, and producing the final craft product. The training was facilitated by the KKN team in collaboration with a resource person from Yayasan Sehati Bengkulu, and held at the house of the RT head. As a symbolic gesture of community involvement and skill acquisition, the finished bag was handed over to the neighborhood leader. While the direct economic impact has not yet been realized due to the early stage of implementation, the activity successfully increased public awareness and interest in waste-based craft making. This initiative demonstrates that with proper education and community engagement, household waste can be transformed into economic opportunities and contribute to environmental sustainability.